Brain Ischemia Activates β- and γ-Secretase Cleavage of Amyloid Precursor Protein: Significance in Sporadic Alzheimer’s Disease - Pluta, Ryszard; Furmaga-Jabłońska, Wanda; Maciejewski, Ryszard; Ułamek-Kozioł, Marzena; Jabłoński, Mirosław (Molecular Neurobiology, 2013)
Amyloid precursor protein cleavage through β- and γ-secretases produces β-amyloid peptide, which is believed to be responsible for death of neurons and dementia in Alzheimer’s disease. Levels of β- and γ-secretase are increased in sensitive areas of the Alzheimer’s disease brain, but the mechanism of this process is unknown. In this review, we prove that brain ischemia generates expression and activity of both β- and γ-secretases. These secretases are induced in association with oxidative stress following brain ischemia. Data suggest that ischemia promotes overproduction and aggregation of β-amyloid peptide in brain, which is toxic for ischemic neuronal cells. In our review, we demonstrated the role of brain ischemia as a molecular link between the β- and the γ-secretase activities and provided a molecular explanation of the possible neuropathogenesis of sporadic Alzheimer’s disease.